Taras Shevchenko’s Сhristian cordocentrism: Християнський кордоцентризм Тараса Шевченка - Bigun, Olga (Przegląd Wschodnioeuropejski, 2020)
The article deals with adoption of Christian tradition in poetry of Taras Shevchenko. Theoretical basis includes methodological principles of hermeneutics, the philosophicoaesthetic approach to art, cross-cultural methods. On the one hand, the sources of the creative components by Shevchenko’s ethics and aesthetics are related in Christian tradition. On the other hand, as a result of cordocentrist intention of the Ukrainian ethnos, Christian canon was deprived of the big part of rigorism in Old-Kyiv period. Shevchenko’s aesthetic theology is insufficiently investigated but it characterizes the absence of stark categories, dogmas and rituals. It gives an opportunity to speak about the apophatic approach in Shevchenko’s dialectic of God-seeking which appears in the apophatic approach of individual style which also you can find in Old Kyivan authors’ works. The outcome of our investigation proves that the Shevchenko’s adoption of Christian tradition shows the priority of aesthetic and cultural landmarks of Kyiv Christianity.